EEE - Extreme Energy Events: an astroparticle physics experiment in Italian High Schools. Issue 8 (May 2016) - Abbrescia, M; Avanzini, C; Baldini, L; Baldini Ferroli, R; Batignani, G; Bencivenni, G; Bossini, E; Bressan, E; Chiavassa, A; Cicalò, C; Cifarelli, L; Coccia, E; et al.
Abstract: The Extreme Energy Events project (EEE) is aimed to study Extensive Air Showers (EAS) from primary cosmic rays of more than 10 18 e V energy detecting the ground secondary muon component using an array of telescopes with high spatial and time resolution. The second goal of the EEE project is to involve High School teachers and students in this advanced research work and to initiate them in scientific culture: to reach both purposes the telescopes are located inside High School buildings and the detector construction, assembling and monitoring - together with data taking and analysis - are done by researchers from scientific institutions in close collaboration with them. At present there are 42 telescopes in just as many High Schools scattered all over Italy, islands included, plus two at CERN and three in INFN units. We report here some preliminary physics results from the first two common data taking periods together with the outreach impact of the project.